Analysis of runway pavement response under aircraft moving load by FEM. Issue 2 (3rd April 2018) - Shafabakhsh, Gholamali; Kashi, Ehsan; Tahani, Mojtaba
Abstract : Purpose: Given the importance of airports and the need to develop this issue in runway, the purpose of this study, pavement response values under loading of different aircraft have been obtained using tire and pavement modeling by finite element method (FEM). To predict the actual behavior of pavements under aircraft loading, dynamic analysis of runway flexible pavement was performed using Abaqus software version 6.10. Design/methodology/approach: The method is based on finite element analysis and software simulation. And the main goal to obtain the amount of pavement stress and deflection at different speeds. Findings: The results of modeling showed that aircraft movement at a speed of 5-8 km/h leads to the highest stresses and deflections in the pavement. Moreover, the effect of elastic modulus variations of the asphalt concrete on the tensile strain under advisory circular layer was calculated for Airbus A380 by using FEM. To validate the results of the runway pavement dynamic analysis, the results of modeling have been compared with the field test results of National Airport Pavement Test Facility. Originality/value: Stresses and deflections of pavement during aircraft movement at different speeds of 5, 8 and 20 km/h on the runway have been presented, and the critical points in length, width and depth of runway pavement, as well as the most critical speed of aircraft in terms of induced damage to the pavement, have been obtained.